2017
DOI: 10.3390/polym9030089
|View full text |Cite
|
Sign up to set email alerts
|

RAFT Polymerization of Styrene and Maleimide in the Presence of Fluoroalcohol: Hydrogen Bonding Effects with Classical Alternating Copolymerization as Reference

Abstract: Abstract:The impacts of hydrogen bonding on polymerization behavior has been of interest for a long time; however, universality and in-depth understanding are still lacking. For the first time, the effect of hydrogen bonding on the classical alternating-type copolymerization of styrene and maleimide was explored. N-phenylmaleimide (N-PMI)/styrene was chosen as a model monomer pair in the presence of hydrogen bonding donor solvent 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP), which interacted with N-PMI via hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Carbon NMR confirmed that the maleimide content of purified products was less than 50%, so 2D HSQC and TOCSY NMR experiments were employed to examine the alternating tendency (see Supporting Information). While previous studies have investigated alternating tendency through studies of reactivity ratios, 24,32 MALDI-TOFS, 33 or through NMR chemical shifts of the backboneadjacent styrene carbon, 34 we used 2D NMR to avoid conflation of monomer sequence peaks with those of the strongly polarizing trimethyl ammonium group adorning the aromatic ring. Maleimide methine protons were found to correlate strongly with the styrenic methylene and methine protons, confirming the presence of alternating sequences along the polymer backbone.…”
Section: Synthesis Of Alternating Polyelectrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon NMR confirmed that the maleimide content of purified products was less than 50%, so 2D HSQC and TOCSY NMR experiments were employed to examine the alternating tendency (see Supporting Information). While previous studies have investigated alternating tendency through studies of reactivity ratios, 24,32 MALDI-TOFS, 33 or through NMR chemical shifts of the backboneadjacent styrene carbon, 34 we used 2D NMR to avoid conflation of monomer sequence peaks with those of the strongly polarizing trimethyl ammonium group adorning the aromatic ring. Maleimide methine protons were found to correlate strongly with the styrenic methylene and methine protons, confirming the presence of alternating sequences along the polymer backbone.…”
Section: Synthesis Of Alternating Polyelectrolytesmentioning
confidence: 99%
“…The complexation of oppositely-charged homopolyelectrolytes is known to result in solid precipitates or liquid coacervates. 22,24,35,36 In this phase separation process, the intricate balance of electrostatic forces and other non-covalent interactions dictates the nature of the resultant bulk complex product. The density, strength, and arrangement of associating groups are particularly important to controlling the dynamics and underlying physics.…”
Section: Solid and Fluid Behavior Of Bulk Polyelectrolyte Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Pfeifer and Lutz first demonstrated the viability of installing distinct maleimides over time during the controlled propagation of polystyrene via atom transfer radical polymerization, 22 which can afford sequence specific polymers via its chain growth writing mechanism. 23 At the molecular level, alternating styrene/maleimide systems have increased chain stiffness 24 and can be easily modified to link pendant groups to the main chain for nonlinear optics, 25,26 supramolecular materials, 27 fluorimetric sensing 28 or polymer electrolytes. 29 However, to the extent of our knowledge, there are no examples to date of bringing this strategy to synthetic designer polyelectrolytes to modulate the physical state of polyelectrolyte complexation.…”
Section: Introductionmentioning
confidence: 99%
“…-hexafluoro-2-propanol (HFIP) was investigated by Zhu and coworkers [20]. In comparison to the toluene (reactivity ratio PMI 0.078, styrene 0.068), considerably different copolymerization parameters were observed in HFIP (reactivity ratio PMI 0.026, styrene 0.050), i.e., a less alternating tendency of the copolymerization was observed.…”
mentioning
confidence: 99%